Royal jelly coordinately enhances hippocampal neuronal expression of somatostatin and neprilysin genes conferring neuronal protection against toxic soluble amyloid-β oligomers implicated in Alzheimer's disease pathogenesis. (December 2018) - Kawahata, Ichiro; Xu, Huinan; Takahashi, Michiyo; Murata, Kiyoshi; Han, Wanying; Yamaguchi, Yoshihisa; Fujii, Akira; Yamaguchi, Kikuji; Yamakuni, Tohru
Graphical abstract: Highlights: DMSO-soluble fraction of royal jelly (DRJ) raises hippocampal neuronal SST level. DRJ increases NEP level in a distinct neuronal subset via SST receptors activation. DRJ prevents toxic Aβ42 oligomers-impaired mRNA expression for SST and NEP. A highly lipophilic fraction from the royal jelly raises both mRNA levels as well. Abstract: Hippocampal somatostatin (SST)-neprilysin (NEP) system functions as a defense system against neurotoxic soluble amyloid-β oligomers associated with onset of Alzheimer's disease. However, it remains unknown whether royal jelly (RJ) could impact the defense system. In this study using primary cultures of hippocampal neurons, including SST-positive and NEP-positive neuronal subsets, we evaluated the ability of DMSO-soluble fraction of RJ (DRJ) to enhance SST and NEP genes expression. The DRJ potently facilitated CRE-mediated transcription, and raised SST-immunoreactivity in an SST-positive neuronal subset, where elevated phospho-CREB immunoreactivity was simultaneously observed. Chromatin immunoprecipitation-qPCR assays uncovered that the DRJ mechanistically facilitated CREB-binding to a CRE present at the promoter region of SST . Moreover, in a distinct NEP-positive neuronal subset, the DRJ led to elevation of NEP immunoreactivity, which was abolished by cyclosomatostatin, a non-selective SST receptors antagonist. Collectively, these findings provide the first evidence that the RJ possesses potential to activate the hippocampal SST-NEP system.